Memory as Social Glue: Close Interpersonal Relationships in Amnesic Patients - Davidson, Patrick S.; Drouin, Héloïse; Kwan, Donna; Moscovitch, Morris; Rosenbaum, R Shayna (Frontiers in Psychology, 2012)
Memory may be crucial for establishing and/or maintaining social bonds. Using the National Social life, Health, and Aging Project questionnaire, we examined close interpersonal relationships in three amnesic people: K.C. and D.A. (who are adult-onset cases) and H.C. (who has developmental amnesia). All three patients were less involved than demographically-matched controls with neighbors and religious and community groups. A higher-than-normal percentage of the adult-onset (K.C. and D.A.) cases’ close relationships were with family members, and they had made few new close friends in the decades since the onset of their amnesia. On the other hand, the patient with developmental amnesia (H.C.) had forged a couple of close relationships, including one with her fiancé. Social networks appear to be winnowed, but not obliterated, by amnesia. The obvious explanation for the patients’ reduced social functioning stems from their memory impairment, but we discuss other potentially important factors for future study.